Constructing Survey Data : an Interactional Approach. - Gobo, Giampietro (SAGE Publications, 2014)
Proposing a post-positivist, interviewee-centred approach, Giampietro Gobo and Sergio Mauceri's new book offers students and researchers a practical introduction to the process of collecting and analyzing survey data.